Penelitian Kemampuan Pemecahan Masalah di Jurnal Pendidikan Matematika: dari Desain Penelitian hingga Analisis Data - Gunawan, Fransiskus Hendra; T, Ahmad Yani; Siregar, Nurfadillah; Meldi, Nadya Febriani; Permanda, Saul (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
Empowering problem-solving skills is one of the many objectives that 21st-century education aims to achieve. This study employs content analysis on a number of articles published in mathematics education journals, with problem-solving skills as the primary focus. The research indicates that over time, the number of publications centered on problem-solving skills has increased. Among these publications, the most dominant research design is qualitative. Tests and interviews are the most commonly used data collection instruments. Based on the findings of this research, several recommendations have been proposed for future studies that prioritize problem-solving skills. Some of these recommendations include increasing the diversity of research types and selecting more appropriate data analysis techniques.